Pembuatan Aplikasi Simulator Robot Manipulator dengan Menggunakan Forward dan Inverse Kinematic di Unity - Kevin Nathanael Sugiharto; Iwan Njoto Sandjaja; Handry Khoswanto (Jurnal Infra, 2018)
Robot manipulator is a technology that is widely used in all life applications. Because of the widespread use of robot manipulators, it is given robotics learning for students interested in robotics in Electrical Engineering courses. The price of the robot is relatively expensive and the existence of mathematical calculations become obstacles.This thesis is made to answer the above problem. This application is made with Unity engine with C # programming language. This application simulates the movement of robots either forward or inverse kinematic with the limits of DOF 2 and 3. A similar application that is a comparison is RoboAnalyzer.Based on the test results, the program 'FIK' has described the forward and inverse kinematik, mathematical formula calculation, simulator movement, and the resulting trace. For kinematic inverse results only show one result, whereas in the comparison program display the possibility of 2-4 answers.